2009
DOI: 10.1098/rspb.2009.0896
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the root of bilaterian animals with scalable phylogenomic methods

Abstract: A clear picture of animal relationships is a prerequisite to understand how the morphological and ecological diversity of animals evolved over time. Among others, the placement of the acoelomorph flatworms, Acoela and Nemertodermatida, has fundamental implications for the origin and evolution of various animal organ systems. Their position, however, has been inconsistent in phylogenetic studies using one or several genes. Furthermore, Acoela has been among the least stable taxa in recent animal phylogenomic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
648
6
11

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 682 publications
(700 citation statements)
references
References 36 publications
35
648
6
11
Order By: Relevance
“…First, sipunculans traditionally have been considered a distinct animal phylum (Sedgwick, 1898;Hyman, 1959;Clark, 1969;Stephen and Edmonds, 1972;Rice, 1985;Saiz-Salinas, 1993;Cutler, 1994;Valentine, 1997;Strand et al, 2010). However, a series of molecular hypotheses show accumulative support for the inclusion of sipunculans within the annelid radiation (McHugh, 1997;Boore and Staton, 2002;Struck et al, 2007;Dunn et al, 2008;Struck et al, 2011), as one of the earliest diverging annelid lineages (Dordel et al, 2010;Hejnol et al, 2009;Struck et al, 2011;Weigert et al, 2014), suggesting that Annelida should be recognized as one of the most biologically diverse clades within Spiralia http://dx.doi.org/10.1016/j.ympev.2014.10.019 1055-7903/Ó 2014 Elsevier Inc. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, sipunculans traditionally have been considered a distinct animal phylum (Sedgwick, 1898;Hyman, 1959;Clark, 1969;Stephen and Edmonds, 1972;Rice, 1985;Saiz-Salinas, 1993;Cutler, 1994;Valentine, 1997;Strand et al, 2010). However, a series of molecular hypotheses show accumulative support for the inclusion of sipunculans within the annelid radiation (McHugh, 1997;Boore and Staton, 2002;Struck et al, 2007;Dunn et al, 2008;Struck et al, 2011), as one of the earliest diverging annelid lineages (Dordel et al, 2010;Hejnol et al, 2009;Struck et al, 2011;Weigert et al, 2014), suggesting that Annelida should be recognized as one of the most biologically diverse clades within Spiralia http://dx.doi.org/10.1016/j.ympev.2014.10.019 1055-7903/Ó 2014 Elsevier Inc. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Nextgeneration sequencing (NGS) now enables us to generate large data sets for many species at a relatively low cost. The systematic community has necessarily progressed from candidate genes through EST-based methods to 454 and Illumina-based transcriptome and genome datasets to resolve major relationships among the animal phyla (e.g., Dunn et al, 2008;Hejnol et al, 2009;Nosenko et al, 2013;Ryan et al, 2013;Moroz et al, 2014). Long outstanding issues have been resolved for within-phylum relationships among arthropods, molluscs, and annelids, to mention just some of the largest animal phyla (e.g., Meusemann et al, 2010;Kocot et al, 2011;Smith et al, 2011;Struck et al, 2011;von Reumont et al, 2012;Andrade et al, 2014;Weigert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent uncontaminated ribosomal RNA analyses placed Xenoturbella surprisingly among the deuterostomes (Paps et al 2009b;Philippe et al 2007;Bourlat et al 2003). However, later phylogenomic studies including EST data suggested Xenoturbella to be a sister group of Acoelomorpha together forming the sister group to the rest of bilaterians (Hejnol et al 2009).…”
Section: A Contrasting Hypothesis: Acoelomorphs Are Deuterostomesmentioning
confidence: 99%
“…This study considered four different lines of evidence: mitochondrial protein coding genes, nuclear-coding phylogenomic analyses (a subset of the genes used by Hejnol et al 2009), microRNA content, and the absence/ presence of the gene Rsb66. All these datasets provided weak evidence for the deuterostome affiliation of Acoelomorpha and Xenoturbella.…”
Section: A Contrasting Hypothesis: Acoelomorphs Are Deuterostomesmentioning
confidence: 99%
See 1 more Smart Citation